Differences in cognitive functions between cytomegalovirus-infected and cytomegalovirus-free university students: a case control study - Chvátalová, Veronika; Šebánková, Blanka; Hrbáčková, Hana; Tureček, Petr; Flegr, Jaroslav (Scientific reports, 2018)
Cytomegalovirus (CMV) is the herpetic virus, which infects 45-100% people worldwide. Many reports suggest that CMV could impair cognitive functions of infected subjects. Here we searched for indices of effects of CMV on infected subjects' intelligence and knowledge. The Intelligence Structure Test I-S-T 2000 R was used to compare IQ of 148 CMV-infected and 135 CMV-free university students. Infected students expressed higher intelligence. Paradoxically, their IQ decreased with decreasing concentration of anti-CMV antibodies, which can be used, statistically, as a proxy of the time passed from the moment of infection in young subjects when the age of subjects is statistically controlled. The paradox of seemingly higher intelligence of CMV infected subjects could be explained by the presence of the subpopulation of about 5-10% CMV-positive individuals in the population of "CMV-negative students". These false negative subjects had probably not only the oldest infections and therefore the lowest concentration of anamnestic antibodies, but also the lowest intelligence among the infected students. Prevalence of CMV infection in all countries is very high, approaching sometimes 90%. Therefore, the total impact of CMV on human intelligence may be large.
Keywords: Cytomegalovirus; inteligence; univerzity; studenti; Universities; Intelligence Tests; Male; Cytomegalovirus Infections; lidé; Humans; Models, Theoretical; Health Knowledge, Attitudes, Practice; Biomarkers; Students; Intelligence; kognice; mužské pohlaví; ochrana veřejného zdraví; zdraví - znalosti, postoje, praxe; inteligenční testy; cytomegalovirové infekce; Public Health Surveillance; Cognition; biologické markery; Case-Control Studies; ženské pohlaví; Female; studie případů a kontrol; teoretické modely